Introduction of innovating techniques in the Sahelian earth dams: presentation of the different techniques - (:unkn) unknown (My University, 1989)
Relying on a rich experience of small earth dams found in Burkina Faso, the report is an analysis of a number of technical problems encountered on this type of installations. For each problem, technical solutions, tested for their efficiency in France, and adapted to Sahelian Africa are suggested in interesting economic conditions. The main points covered concern foundation tightness, upper and lower bank protection, embankment compaction (with natural water content), sizing and selection of the type of spillways.
Keywords: African Research